2017
DOI: 10.1039/c7py00241f
|View full text |Cite
|
Sign up to set email alerts
|

Donor–acceptor polymers with tunable infrared photoresponse

Abstract: NIR-SWIR photoresponsive donor–acceptor polymers enable the detection of infrared light when incorporated into bulk heterojunction photodiodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 59 publications
3
79
0
Order By: Relevance
“…As shown in Figure 2e, the Azoulay lab synthesized a series of donor−acceptor conjugated polymers with variations in the acceptor moieties, which allowed tuning of the semiconductor energy levels. 18 Leveraging this series of materials, the Ng lab demonstrated devices with spectral response up to 1700 nm. 28,29 Figure 2f displays an organic bulk heterojunction (BHJ) photodiode 30,31 that comprises an SWIR-responsive organic semiconductor used as the p-type donor intermixed with an ntype [6,6]-phenyl-C 71 -butyric acid methyl ester (PCBM[70]) acceptor.…”
Section: Infrared-responsive Organic Semiconductors and Device Structmentioning
confidence: 99%
“…As shown in Figure 2e, the Azoulay lab synthesized a series of donor−acceptor conjugated polymers with variations in the acceptor moieties, which allowed tuning of the semiconductor energy levels. 18 Leveraging this series of materials, the Ng lab demonstrated devices with spectral response up to 1700 nm. 28,29 Figure 2f displays an organic bulk heterojunction (BHJ) photodiode 30,31 that comprises an SWIR-responsive organic semiconductor used as the p-type donor intermixed with an ntype [6,6]-phenyl-C 71 -butyric acid methyl ester (PCBM[70]) acceptor.…”
Section: Infrared-responsive Organic Semiconductors and Device Structmentioning
confidence: 99%
“…To further push the spectral response above 1200 nm, some groups, including our group, focused on D–A polymers with ultralow bandgaps . Although these ultralow‐bandgap polymers absorb in the NIR region and above 1200 nm, due to the low bandgap and lowest unoccupied molecular orbital (LUMO) energy levels, the EQE and spectral response of the corresponding devices in the NIR region or above 1200 nm are too low to be meaningfully useful for imaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…The BHJ is formed via blending two organic semiconducting polymers (a donor and an acceptor) with different chemical potential energies. Existing BHJ organic photodetectors exhibit a relatively wide spectral response (0.3–1.8 μm), detectivities ( D *) ≈ 10 12 Jones, and a linear dynamic range over 100 dB in the visible range (0.5–0.8 μm) . For example, Gong et al reported a high‐detectivity polymer photodetector with wide spectral response from 300 to 1450 nm using a narrow‐bandgap semiconducting polymer blended with a fullerene derivative.…”
Section: Materials and Devices For High‐performance Sensingmentioning
confidence: 99%